Do Animals Go to Heaven? Medieval Philosophers Contemplate Heavenly Human Exceptionalism - Joyce E. Salisbury (Athens Journal of Humanities & Arts, 2014)
Beginning in about the second century C.E., Christian philosophers reflected upon the nature of human beings, our purpose on earth, and our path to the promised afterlife. In the course of these reflections, they considered our relationship to nature, and the non-human animals that share our world. Most thinkers accepted a Biblical mandate of ‘mastery’ to explain that humans should have dominance over animals, but that only described this world, not the next. Most theologians asserted that humans were exceptional because they had ‘reason,’ and most early Christians established a correlation between ‘reason’ and ‘soul.’ This meant that for them animals had no soul so there was no place for them in heaven. The question of immortality might have remained unambiguously in the hands of humans if theologians believed that only our souls were immortal. As soon as theologians concluded that our flesh would join our souls in heavenly reward, the door was opened for animals to enter into paradise. For, after all, animals had bodies and flesh just as humans do. Some thinkers argued that just as human bodies will be transformed for salvation, animal bodies, too, can be redeemed and changed to enjoy an afterlife. For these theologians, God is prepared to save His whole creation – plants and animals -- and we will all enjoy the next life. This paper traces the various ideas about animals in heaven and suggests that these attitudes towards heaven reveal what we think about animals, humans, and the web of life.